Ultra-low-field magneto-elastocaloric cooling in a multiferroic composite device - Huilong Hou (Nature Portfolio, 2018)
The broad use of elastocaloric materials in cooling applications is hindered by the need to exert large forces onto the material. Compressing a magnetostrictive-elastocaloric composite using a low magnetic field of 0.16 T, temperature changes up to 4 K are achieved without applying external forces.